Membahasakan Gerakan Antikorupsi dalam Tri Darma Perguruan Tinggi: Sebuah Refleksi - Muhammad Yunus Anis (Jurnal Perkotaan, 2017)
Corruption is a trouble and critical disease which has to get the amputation as soon as possible from the deep of the point of problems. This condition has become the main reason why this article should be written. How very dangerous is the effect of the corruption, until some people afraid if there is someone called the name of “Indonesia”, they just remember about the corruption. Thus, the college as the main place to get the seedbed of academicians had to be ready to face the greatest spreading of corruption effects. The readiness of the college to be opposed to corruption movement can be implemented from the three main principles of the college, such as: (1) the process of education, (2) the process of research, and (3) the process of dedication toward society.